Constraints-led learning in Practice: Designing effective learning environments - Renshaw, I.; Headrick, J.; Maloney, M.; Moy, B.; Pinder, R. (Skill acquisition in sport: research, theory and practice, 2020)
Adopting the constraints-led approach requires significant thought in terms of which constraints to add. Due to the complexity of nonlinear systems it is difhicult to predict the behaviours that are likely to emerge in learners given the need to account for the `delicate` and dynamic interaction of environment, task and individual constraints in any learning event. The importance of in-situ studies highlights the value of sport scientists and practitioners working together to identify and design key constraints. In an attempt to address these issues, Orth, Button, and van der Kamp (2018) suggest that practitioners can use systematic and unsystematic approaches to the manipulation of constraints. By adopting a systematic approach, practitioners can treat the constraint that they choose to manipulate as a potential control parameter, which can be scaled up or down to measure its impact on a performance variable. There is still a place for the unsystematic manipulation of constraints where practitioners constantly and randomly manipulate task and environmental constraints. For example, manipulations of tennis surfaces, ball characteristics (i.e., sizes, types, mass), court sizes and net heights could be designed into sessions to support the individuals` exploration of the sport they are working within. In conclusion, we have attempted to show how the constraints-led approach can be used by practitioners across a range of sports, with performers at different stages on the developmental continuum. However, it should be clear from the above examples that simply adopting this approach should not be seen as a panacea for practitioners. Adopting a constraints-led approach in teaching and coaching practice that will lead to effective interventions is therefore subject to che same requirements when designing learning activities or when providing prescriptive instructions.